Is dermoscopy helpful in differentiating alopecia areata from other forms of alopecia?. Issue 7 (July 2016) - Adam, Patricia; Ajibade, Oluwakemi
Abstract : Evidence‐Based Answer : The presence of tapering hairs on dermoscopy is the most useful finding to differentiate alopecia areata from other forms of alopecia (100% specificity). The presence of black dots, broken hairs, and trichorrhexis nodosa may also be diagnostically useful (SOR: C, 1 cross‐sectional study and 1 case‐control study, both at high risk of bias).